Analisis Variasi Bahan terhadap Kualitas Pupuk Organik Cair (POC) Dari Sisa Makanan - Nabila Nurulita Maghfirani; Novitri, Nora Amelia; Vivin Setiani; Indra Lesmana (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2024)
A The generation of food waste is increasing along with the times. Food waste that is not processed properly will increase carbon emissions from the degradation of the waste. Therefore, proper processing is needed to reduce the generation of food waste. One method of processing food waste is to process food waste into liquid organic fertilizer (LOF) through an anaerobic fermentation process. In this research, food waste was processed into LOF using the fermentation method. This fermentation was carried out for 12 days without the presence of oxygen. In this study, there were variations in stirring to analyze the comparison of LOF results with these variations. Apart from that, food waste is mixed with goat and cat feces. This dirt can increase levels of nitrogen, phosphorus and potassium in the LOF. Analysis of LOF quality parameters in this study consisted of C-organic, phosphorus, potassium, N-total, and pH. The results of this research showed that pH of LOF met LOF quality standard based on the degree of the Minister of Agriculture No. 261 2019. The results of the MANOVA (Multivariate Analysis of Variance) test show material variations affected all dependent variables with a significance value of Î± < 0,05. The best variation was 40% cat feces and 60% food waste that produced the highest total NPK.